Commentary: IARC Monographs Program and public health under siege by corporate interests. Issue 4 (3rd February 2018) - Infante, Peter F.; Melnick, Ronald; Vainio, Harri; Huff, James
Abstract : The International Agency for Research on Cancer (IARC) evaluates causes of cancer with help from independent international experts in an open and transparent manner. Countries, research and regulatory agencies, and other organizations adopt IARC evaluations for communication of human cancer hazards, and for strategies to prevent cancer. Scientists worldwide endorse IARC cancer evaluations and process. Those with economic interests, however, challenge IARC's cancer evaluations, most recently for glyphosate and red and processed meats, and are conducting a campaign including intervention from US Congressional Representatives to discredit IARC's review process and to undermine financial support—a campaign intimidating to IARC and Working Group members. Challenges to scientific interpretations serve to advance science and should be resolved by scientific experts who do not have conflicts of interest. Such interference does not bode well for the free flow of scientific information that informs and protects the public from risks of cancer.